(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
The perfluoroalkyl substances (PFASs) residues, which come from environmental pollution, tend to accumulate in the food chain (EFSA, 2008; Guerranti et al., 2013). 17 chemicals of PFASs family were selected for this study. Fresh pork samples were extracted by Waters® WAX SPE (solid phase extraction) cartridges. All extracted samples were analyzed by liquid chromatography tandem mass spectrometry (LC-MS/MS). The results of calibration curves of each PFAS were good, the R2 values ranging from 0.9901 to 0.9993. The Recoveries were in the range 80%-119%. The protocol of extraction by Waters® WAX SPE cartridge will be applied in future studies.